Information Technology-Based Public Service Innovation Management Strategy: A Case Study of Mobile Application Usage in Government Agencies - Nurjannah, Ulva; Hasymi, Edi; Putera, Roni Ekha (LPPM Universitas Ekasakti, 2025)
This examination explores how innovation is strategically managed in public services that leverage information technology, with a primary focus on the significance of mobile applications within governmental entities. The call for better public services is rooted in the significant need to enhance efficiency, effectiveness, and service quality by leveraging digital technologies. This inquiry focuses on understanding how mobile applications act as facilitators for innovation in public service delivery and investigates the variables that may either promote or hinder the success of these innovations. The investigation's methodology is qualitative, involving data collected through interviews, direct observations, and reports from governmental entities that have integrated mobile applications. The research shows that mobile applications can optimize service delivery, enhance transparency, and widen public access to governmental services. In any case, the fruition of this artistic venture is closely linked to the engagement of leadership, the preparedness of skilled workers, the adequacy of technological resources, and the dynamic involvement of the masses. The identified hurdles range from poorly equipped training for human resources to an unwillingness to adapt to organizational changes and a lack of proper technological infrastructure. This study advocates for enhancing human resource capabilities, improving communication among stakeholders, and developing adaptive and user-friendly technological systems to ensure the sustainability of mobile application-based public service innovations and to maximize the value added to the public. Consequently, strategic and integrated innovation management is essential for the digital transformation of public services in the contemporary era.